Interference analysis of WiMAX and DVB-T systems: article / Nurul Novia Abd Razak - Abd Razak, Nurul Novia (2013)
With the increasing development of wireless systems, frequency utilization is limited by the problem of insufficient spectrum. More portion of the spectrum is needed to cope with the increasing demand of the 3G and 4G technologies. On the other hand, analogue TV is shifting to digital and after this switch-over there is some part of the spectrum that free. Thus, the objective of this research is to investigate the interference of the coexistence on DVB-T and WiMAX systems. We design an interference analysis to find out realistic distance between the DVB-T transmitter and WiMAX receiver. We consider a scenario where the DVB-T transmitter is located together with a WiMAX system in very close proximity. We evaluate and analyze the performance due to the separation distances between the two systems in terms of transmission power, capacity and the signal strength. Simulations results have shown that at 40 km distance, there is no interference between the transmission.